2024 Election Reflections: Political Ambition and Legal Defeat - Siti Handayani Herdiyanti; Dhea Alfie; Feri Irawan; Gilang Respati; Imas Rosidawati Wiradirja (International Journal of Scientific Multidisciplinary Research, 2024)
The 2024 election in Indonesia faces significant challenges related to political ambitions and legal defeats, which have impacted the integrity and implementation of the election process. Political ambitions from candidates and political parties often lead to violations of election rules, including the spread of misleading information and manipulation of voting results. Legal defeats, such as violations of campaign rules and the inability of law enforcement to handle these cases, undermine public trust in the democratic system and law enforcement institutions. This article examines the impact of these legal defeats and provides recommendations for reforms in election regulations, increased law enforcement, transparency, and political education. Comprehensive reform efforts are needed to ensure fair elections and increase public trust in the democratic process in the future